Novel Anticancer Strategies - Bousbaa, Hassan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Novel Anticancer Strategies reviews important findings and updates within the cancer therapy field, of great interest to those in academic research studying the development and validation of novel anticancer approaches. The Editor invited preeminent specialists to contribute to original and review articles devoted to key areas of major progress and expectations. Key features: Nanoparticle-based drug delivery in cancer therapy; Extracellular vesicles for anticancer drug delivery; Peptide-based drug conjugates; Cancer stem cells as a valuable target to eradicate tumor relapse; Spheroids in preclinical model for cancer research; and cancer immunotherapy.